Bullying in the healthcare workplace: a cross-sectional study among Nigerian physiotherapists - Ifeoma Uchenna Onwuakagba; Ebubechukwu Ogochukwu Uchendu; Sochima Johnmark Obiekwe; Favour Chidera Kanu; Ifeoma Adaigwe Amaechi; Anita Chinwendu Okafor; Christopher Olusanjo Akosile; Emmanuel Chiebuka Okoye (Bulletin of Faculty of Physical Therapy)
Abstract Background Workplace bullying (WPB) can impact the overall well-being of healthcare professionals as well as the care provided to patients. There are no available studies on the prevalence of WPB among physiotherapists, especially in Nigeria. Objective This study aimed to investigate the prevalence of WPB and its associated factors among clinical physiotherapists in Nigeria. Method This cross-sectional study was conducted among 372 Nigerian clinical physiotherapists conveniently recruited at various hospitals. Data was obtained using an adapted self-administered questionnaire and the Negative Acts Questionnaire-Revised (NAQ-R). Results The prevalence of bullying was 42.1%, with participants reporting repeated experiences within the previous 6 months. A high proportion of participants (83.1%) witnessed someone else being bullied at their workplace. The majority of the bullying incidents involved superiors targeting subordinates (83.7%). Participants reported that the most prevalent forms of bullying were verbal aggression (64.4%), followed by intimidating acts (59.4%), insulting remarks, gossip (58.3%), mind games (29.8%), and neglect of opinions (37.6%). No significant associations were found with gender (p = 0.632), religion (p = 0.151), marital status (p = 0.085), ethnicity (p = 0.896), educational attainment (p = 0.150), or rank (p = 0.091). However, significant associations were identified between WPB and years of practice (p = 0.041), and organization of employment (p < 0.001). Conclusion The observed prevalence of WPB among Nigerian clinical physiotherapists is of great concern. Targeted interventions and policy developments are highly recommended to create a safer work environment.